(3QSGdI aj QHY GdTcGRjIs - (3GHf GdeLOj , TgGH GdOjf CHh GdYHGS Hf GdeLOj,J (B850 (3g` s
(3ChdgG (B:s
(3HYO GdOjHGLI (B: (3aEf ef JbOe ef CYjGf YdeGA GdUfGYI bO GSJfJLhG ef GdOSJhQ eG GcJai HQHY CQHGYg hSehg GdQHY GdeLjH s
(3BNQgG (B:s
(3EPG cGfJ GdTeS ai NeS OQL ef GdCSO , jWdY GdTYQi GdYHhQ HeUQ YfO GdaLQ (B[ (3GdfU ebWhY gfG hdjS JGe (B] s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B125 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B221s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B128 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B42 s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdadcs